PEAK: Literature Review of the Interventions Based on Stimulus Equivalence and RFT for People with Atypical Development - Marquetti, Izaniele; Gonçalves, Yanne R.; Amaral, Ana Raquel Q. (Perspectivas em Análise do Comportamento, 2021)
PEAK is a behavioral assessment and intervention instrument with an innovative proposal. This article aimed to investigate the possibilities of PEAK equivalence and transformation modules (RFT) as a tool of intervention. The timespan of selected data was from 2014 to 2019. The search was initially carried out on the official website of the instrument and later expanded to journals of the area. The search expressions were “PEAK”, “equivalence”, and “transformation”. The results showed that the curriculum was effective for teaching different populations such as people with autism, Down syndrome, and intellectual disability. Different contents were taught, such as academic skills, sensory system relations, and more complex skills in language and perspective. As limitations, it was observed the age of the participants and the fact that the majority of studies was carried out by the research group of the author of the instrument. Further investigations are suggested.